HOW UNIVERSITY EFL LEARNERS PERCEIVE GRAMMAR IN PRODUCTIVE SKILLS - Juwita, Marisa; Jailani, Ahmad; Kurniati (As-Sulthan Journal of Education, 2025)
This study explored English education students' perceptions of Grammar in Productive skills. Using qualitative approach, the study had 25 university students as participants selected through purposive sampling. The data were collected using an interview, and then analyzed using qualitative analysis. The findings of the study revealed that some students consider grammar as a very important aspect in productive skills. However, there is also flexibility in the use of grammar. As in speaking, grammar is used depending on the context whether formal or informal. In addition, many students said that they always have difficulties in using grammar often caused by lack of vocabulary, anxiety in speaking, and lack of confidence.